Detailed numerical simulations of pore competition in idealized micro-spall using the VOF method. (15th July 2019) - Malan, L.C.; Ling, Y.; Scardovelli, R.; Llor, A.; Zaleski, S.
Highlights: Cavitation in micro-spall is modelled using a free-surface approach with multiple bubbles in an incompressible liquid. When the liquid is pulled outwards, bubbles expand. All bubbles do not expand at the same rate and some even shrink until collapse. The number of bubbles "surviving" can be characterized by the Weber number. Abstract: Under shock loading, metals have been found to melt and with reflection of the shock wave from the material free surface, cavities nucleate and grow. This process is referred to as microspalling and has been the topic of several experimental investigations. Measurements during the cavity growth phase are not possible at present and we present here a Detailed Numerical Simulation of an idealized problem where we assume an inviscid, incompressible liquid subject to a constant expansion rate with cavities at a vanishing vapour pressure. To allow for a time-varying gas volume a free-surface interface condition has been implemented in an existing incompressible multiphase Navier–Stokes solver, PARIS, using a Volume-Of-Fluid method. The gas flow remains unsolved and is instead assumed to have a fixed pressure which is applied to the liquid through a Dirichlet boundary condition on the liquid-gas interface. Gas bubbles are tracked individually, allowing the gas pressure to be prescribed using a suitable equation of state. Simulations with hundreds of bubbles have been performed in a fixed domain under a constant rate of expansion. A bubble competition is observed: larger bubbles tend to expand more rapidly at the demise of smaller ones. The time scale of this competition is shown to depend on the Weber number.